2009
DOI: 10.1186/1758-2555-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of biomechanics in the understanding of normal, injured, and healing ligaments and tendons

Abstract: Ligaments and tendons are soft connective tissues which serve essential roles for biomechanical function of the musculoskeletal system by stabilizing and guiding the motion of diarthrodial joints. Nevertheless, these tissues are frequently injured due to repetition and overuse as well as quick cutting motions that involve acceleration and deceleration. These injuries often upset this balance between mobility and stability of the joint which causes damage to other soft tissues manifested as pain and other morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 230 publications
(202 reference statements)
1
87
1
7
Order By: Relevance
“…A tendon, a group of fibrous bundles, is surrounded by a thin connective tissue sheath (epitenon), which is even surrounded by other loose connective tissue layer (paratenon). 20,22,29 Collagen fibrils present an elongated shape when they are stretched and a crimped, waveform appearance when they are no stretched, as observed in Figs. 1c and 1d.…”
Section: Structure and Function Of Tendonsmentioning
confidence: 77%
See 1 more Smart Citation
“…A tendon, a group of fibrous bundles, is surrounded by a thin connective tissue sheath (epitenon), which is even surrounded by other loose connective tissue layer (paratenon). 20,22,29 Collagen fibrils present an elongated shape when they are stretched and a crimped, waveform appearance when they are no stretched, as observed in Figs. 1c and 1d.…”
Section: Structure and Function Of Tendonsmentioning
confidence: 77%
“…16,29,43 The maximum force, maximum strain, stiffness and Young's modulus depend on the thickness and collagen content of the studied tendon type, patient gender and age. 20,29,43 Mechanical experiments using several tendons reported Young's modulus values in the range of 1-2 GPa; ultimate stress values in the range of 50-100 MPa; ultimate strain values of 4-10% and toughness values in the range of 1000-4500 J/kg. 29,43 …”
Section: Structure and Function Of Tendonsmentioning
confidence: 98%
“…It is known that healing capacity of injuries due to ruptures of ligament structures from the bone adhesion is higher than the injuries occurring in any other point on the ligament (12). In a recent study investigating healing potentials according to the anatomic localization of MPFL rupture after the first patellar dislocation, it was reported that good results after conservative treatment were obtained only for MPFL ruptures in the place of adhesion to the patella.…”
Section: Discussionmentioning
confidence: 99%
“…As a full recovery to its pre-injury abilities does not occur, the joint is subjected to instability. This inevitably leads to biomechanical changes across joint surfaces, increasing the risk for degenerative changes and the development of osteoarthritis [24,28,32,33]. In few cases, through a three-stage overlapping healing process (hemorrhage with inflammation, cellular and matrix proliferation and finally, remodeling and maturation), the body may be able to repair the injury enough for a full clinical recovery of the initial structural/functional abilities (i.e., strength and ability to stabilize the joint), but this healing process can take months to resolve itself and underlying instability may still be present.…”
Section: Ligament Response To Injury and Healing Processmentioning
confidence: 99%